2021
DOI: 10.1016/j.arth.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A Crossover Randomized Trial of Visual Abstracts Versus Plain-Text Tweets for Disseminating Orthopedics Research

Abstract: Background: Scientists, surgeons, and trainees are increasingly taking an active role on Twitter to find, disseminate, and exchange knowledge. The purpose of this study was to determine if peer-reviewed journal articles shared on Twitter using visual abstracts (VAs) improve user engagement compared with plain-text tweets. Methods: A two-arm randomized controlled trial with crossover was performed. Manuscripts from the Journal of Arthroplasty were allocated to one of two arms and disseminated via the journal Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In another randomized crossover trial including 50 articles, Hoffberg et al (2020) found that tweets with a visual abstract were associated with a significantly higher number of impressions, retweets, and link clicks compared with textonly abstract tweets (Hoffberg et al, 2020). Additional studies have found further evidence of positive performance of visual abstracts on Twitter compared to text tweets or figures from the paper in the fields of urology (Koo et al, 2019), nephrology (Oska et al, 2020), and orthopaedics (Chisari et al, 2021). Based on this small body of research, it appears that graphical abstracts do outperform text-based posts on Twitter, which may explain the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…In another randomized crossover trial including 50 articles, Hoffberg et al (2020) found that tweets with a visual abstract were associated with a significantly higher number of impressions, retweets, and link clicks compared with textonly abstract tweets (Hoffberg et al, 2020). Additional studies have found further evidence of positive performance of visual abstracts on Twitter compared to text tweets or figures from the paper in the fields of urology (Koo et al, 2019), nephrology (Oska et al, 2020), and orthopaedics (Chisari et al, 2021). Based on this small body of research, it appears that graphical abstracts do outperform text-based posts on Twitter, which may explain the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…According to the aforementioned study on online engagement, healthcare professionals interacted more actively with the inclusion of a GA rather than an abstract or an article title (45.3 times vs. 29.4 times or 28.8 times, respectively). The effect of GAs encouraging online engagement in social media has been confirmed in several medical disciplines, including orthopedics, nephrology, psychiatry, and gastroenterology [13,[17][18][19].…”
Section: Are Gas Really Effective In Increasing the Dissemination Or ...mentioning
confidence: 93%
“…Think it through-There are many successful strategies to effectively communicate your main message in 280 characters or more. Including a visual abstract or key figure that best represents the scope of the paper has been shown to led to increased post engagement, and could be a good strategy to drive engagement with your target audience 20 . Professional tools like Biorender(R), Adobe Suite, or Inkscape are useful to generate these images for both journal publications and social media posts.…”
Section: Linearized Workflow For Twitter Post Constructionmentioning
confidence: 99%